Antioxidant activities of phosphorylated pumpkin polysaccharide - Chen, Ling; Huang, Gangliang (International journal of biological macromolecules, 2019)
Pumpkin polysaccharide was extracted with hot water, and it was chemically modified with phosphorus oxychloride-pyridine to obtain phosphorylated pumpkin polysaccharides (PP1, PP2) with different degrees of substitution. The degree of substitution of PP1 and PP2 was 0.01 and 0.02, respectively. The scavenging effect of pumpkin polysaccharide and its phosphorylated pumpkin polysaccharides on superoxide anions was determined by pyrogallol autooxidation. The scavenging effect of pumpkin polysaccharide and its phosphorylated pumpkin polysaccharide on hydroxyl radicals was determined by salicylic acid method. The reducing ability of pumpkin polysaccharide and its phosphorylated pumpkin polysaccharide was studied. It showed that the phosphorylated pumpkin polysaccharides with different degrees of substitution had higher scavenging ability to hydroxyl radicals and superoxide anions than the underivatized pumpkin polysaccharide.